128k views
5 votes
Consider the equation below. 4(x - 4) + 6x = 14 Part A: Enter the value for x that makes the equation true. X = Part B: Explain the algebraic steps you took to get the solution. thea Part C: Explain how you know your solution in Part A is correct.

User Aliyah
by
4.8k points

1 Answer

2 votes

Part A) To find out the value for x that makes it an identity, (true), we need to solve it.

4(x-4) +6x=14 Distiribute

4x -16 +6x = 14 Combine like terms

2x -16 = 14 Add 16 to both sides

2x = 30 Divide both sides by 2

x =15

Part B) Above explained.

Part C) We can know it by plugging it into the original equation:

4(15 -4) +6(15) = 14

4(11) +90 = 14

44

User Woblob
by
4.6k points